Neurocommunicative factors in the dissemination of fake news supported by photographs (Revista de Investigaciones Universidad del Quindío, 2022)
From the concept of archive image, used by the media to illustrate news and be able to provide visual support for its effective use in mainly audiovisual environments, the fact that images imply truthfulness has been installed in the modern practice of fake news, with continuous and constant examples of affirmations supported in social networks by decontextualized, old visual material, or both. The creation of tests is being carried out to convince the user of false realities, generally corresponding to the author's ideological satisfaction needs.The main objective is to determine the type of relationship between media information and communication in social networks based on the role that journalistic photography plays in relation to neuro-communication.The methodology will be based on an inductive-deductive process of analysis of the type of message that reaches the recipients from the photographs published on social networks.
Keywords: Photography; Fake news; Neurocommunication; Disinformation; Post-truth